Effect of Graphene Reinforcement on the Color Stability of Polymethyl Methacrylate Provisional Restorative Material – An in vitro Study - Vaishnavi Banode; Saee Deshpande; Neelam Pande (Journal of International Clinical Dental Research Organization)
Background: The main concern in the cases of long-term provisionalization in the anterior region of the mouth is staining and discoloration of restorative material that keeps the patients returning to the dentist repeatedly, increasing the number of visits and costs. Recently, graphene-reinforced acrylic resin has been recommended for provisionalization. However, data on its color stability are lacking. Materials and Methods: A total of 72 samples, 24 samples from each restorative material (n = 8), each measuring 10 mm in diameter and 2 mm in thickness, were fabricated from the provisional materials and were divided into three subgroups each into artificial saliva, tea solution, and sambhar solution. Spectrophotometric analyses were performed for 30 and 60 days, respectively. Data were analyzed to compare the correlation of the groups using a one-way analysis of variance and Tukey’s post hoc test (P < 0.005). Results: The maximum mean ΔE values were seen for sambhar solution followed by tea. The mean (± SD) for self-polymerized polymethyl methacrylate (PMMA) provisional resin was 9.06 (±0.65) for sambhar solution and 6.20 (±0.62) for tea, followed by graphene-reinforced PMMA provisional resin 6.72 (±0.42) for sambhar solution and 4.82 (±0.48) for tea. Heat-polymerized PMMA provisional resin exhibited the lowest ΔE values of 5.71 (±0.45) for sambhar solution and 3.92 (±0.24) for tea after 60-day immersion period in the two staining solutions. Conclusion: Heat-polymerized PMMA provisional resin was the most color stable whereas self-polymerized PMMA provisional resin is the least color-stable provisional restorative material. Among the staining solutions, sambhar solution showed higher staining ability.